Responses of N2O emissions to spring thaw period in a typical continuous permafrost region of the Daxing'an Mountains, northeast China. (1st October 2019) - Gao, Weifeng; Yao, Yunlong; Gao, Dawen; Wang, He; Song, Liquan; Sheng, Houcai; Cai, Tijiu; Liang, Hong
Abstract: In the context of global climate warming, spring thaw period had been changed in the permafrost regions, which significantly affect heat and water dynamics, along with soil microbial community structure and diversity, and microbially-mediated nitrogen cycle changes. However, in - situ N2 O emission research is scarce in the permafrost regions and the drivers of N2 O emission during spring thaw period remain unclear. We selected three type of swamp forests in the permafrost region to investigate the N2 O emissions during spring thaw period from 17 March to 23 May 2017. We found that N2 O emission ranged from −35.75 to 74.17 μg m −2  h −1 in the permafrost region during spring thaw period, and there was no significant large burst of N2 O emissions as observed in other ecosystems. The N2 O emission during spring thaw period were lower than those from growing season, which were significant affected by soil temperature. During spring thaw period, swamp forest types had no significantly influence on N2 O emissions, which mainly limited by NO3 − -N content. Stepwise multiple linear regression indicated that the air temperature, thawing depth, soil temperature, soil moisture, pH, NH4 + -N, NO3 − -N, TOC, TN, and C/N ratio were the environmental factors which significant effecting the N2 O emissions. In the field campaign, cumulative N2 O emissions were mainly controlled by thawing depth, soil moisture, pH, NH4 + -N, NO3 − -N and TN during spring thaw period. Overall, the results demonstrate that in the permafrost ecosystems spring thaw period is an important source of N2 O emissions. Graphical abstract: Image 1 Highlights: The N2 O emission during spring thaw period were lower than those from growing season. There was no significant large burst of N2 O emission from the permafrost region. The forest types did not significant influence on N2 O flux during spring thaw period. The N2 O emission from the permafrost region were lower than most ecosystems.